Natural zeolite formation in Mongolia: (volcanogenic-sedimentary zeolite) - Tumenbayar, Baatar; Grayson, Robin; Petrova, Vera; Enkhsaikhan, Rentsendorj (Mongolian Geoscientist, 2019)
The genesis of natural zeolite in Mongolia is attributable to the late Mesozoic tectonic-magmatism activity in East Mongolia - Dornod. The numerous volcanoes formed during this activation process were surrounded by Cretaceous depressions with mineralized waters (Na+, K+, Ca+, Мg+, Al+, H+, SO42-, CO32- ,Cl-, O2- etc.). The huge amount of ash (glass) emanating from volcanic eruptions fell into the mineralized waters; the hydrolysis of amorphous (silicon-oxygen) structure of the glassy ash was dispersed by the effects of acid and alkaline in the water and became colloids. With the water composition transformation, the silicon and oxygen ions bonded together to form tetrahedral radicals, so forming a structure built up through low-pressure silicon-oxygen chains to become the spongy, web-like structural “skeletons” of zeolite minerals. This silicon-oxygen net structure has hollow spaces of varying sizes, which generates strong charges inside, capable of pulling in and out ions and molecules of various dimensions. These naturally occurred rocks (zeolite) are referred to as “molecular sieves” functioning as a sort of colander for radicals. In other words, it breathes. By this means, a vast region developed rich in natural zeolites of many different types under the influence of the geological, paleogeographic and crystallographic factors noted above and have the volcanic sediments’ origin. Among these, clinoptilolite, chabazite and mordenite deposits have, according to our research, a strategic significance for our country’s possible chemical pollution and nuclear poisoning (reflected in the next article). Also, it is now very obvious that Mongolia's natural zeolites can be used in many branches like heavy industries, construction, agriculture, livestock and household needs.